Platelet Activating Factor Receptor Activation Improves siRNA Uptake and RNAi Responses in Well-differentiated Airway Epithelia - Sateesh Krishnamurthy; Mark A Behlke; Michael A Apicella; Paul B McCray, Jr; Beverly L Davidson (Elsevier, 2014)
Well-differentiated human airway epithelia present formidable barriers to efficient siRNA delivery. We previously reported that treatment of airway epithelia with specific small molecules improves oligonucleotide uptake and facilitates RNAi responses. Here, we exploited the platelet activating factor receptor (PAFR) pathway, utilized by specific bacteria to transcytose into epithelia, as a trigger for internalization of Dicer-substrate siRNAs (DsiRNA). PAFR is a G-protein coupled receptor which can be engaged and activated by phosphorylcholine residues on the lipooligosaccharide (LOS) of nontypeable Haemophilus influenzae and the teichoic acid of Streptococcus pneumoniae as well as by its natural ligand, platelet activating factor (PAF). When well-differentiated airway epithelia were simultaneously treated with either nontypeable Haemophilus influenzae LOS or PAF and transduced with DsiRNA formulated with the peptide transductin, we observed silencing of both endogenous and exogenous targets. PAF receptor antagonists prevented LOS or PAF-assisted DsiRNA silencing, demonstrating that ligand engagement of PAFR is essential for this process. Additionally, PAF-assisted DsiRNA transfection decreased CFTR protein expression and function and reduced exogenous viral protein levels and titer in human airway epithelia. Treatment with spiperone, a small molecule identified using the Connectivity map database to correlate gene expression changes in response to drug treatment with those associated with PAFR stimulation, also induced silencing. These results suggest that the signaling pathway activated by PAFR binding can be manipulated to facilitate siRNA entry and function in difficult to transfect well-differentiated airway epithelial cells.